Cadmium induces apoptosis of pig lymph nodes by regulating the PI3K/AKT/HIF-1α pathway. (15th March 2021) - Yiming, Lu; Yanfei, Han; Hang, Yin; Yimei, Cong; Guangliang, Shi; Shu, Li
Highlights: The amount of Cd deposition in pig mesenteric lymph node is the largest. Cd reduces the expression of two-phase detoxification enzymes in pig lymph nodes. Cd can regulate PI3K/AKT/HIF-1α signaling pathway to induce apoptosis. Cd changes the mitochondrial fusion/fission genes in pig lymph nodes. Abstract: Objective: This study was aimed to explore the possible mechanism of environmental metal cadmium (Cd) inducing apoptosis of pig lymph nodes. Method: 10 healthy 6-week-old weaned piglets were randomly divided into two groups (n = 5 pigs/group). The control group was fed with a basic diet, and the test group was fed with a basic diet of 20 mg/kg CdCl2 . Results: The Cd deposition in mesenteric lymph nodes (MLN), inguinal lymph nodes (ILN) and submaxillary lymph nodes (SLN) after Cd exposure was 2.37 folds, 1.4 folds and 1.8 folds of the control group, respectively. And the rate of MLN and ILN apoptotic cells in the Cd group was 4.11 folds and 9.18 folds of the control group, respectively. The mRNA levels of SOD1, SOD2, CAT, GPX1 and GSH in the Cd group were reduced. Similarly, the two-phase detoxification enzymes had a significant downward trend. Cd exposure decreased the activities of GSH, GSH-Px, SOD, CAT, and increased H2 O2 and MDA levels. The mRNA and protein levels of Drp1 and Mff in the Cd group were higher than the corresponding control group, and the mRNA and protein levels of Mfn1 and Mfn2 were lower than those in the control group. In addition, the mRNA and protein levels of pro-apoptotic genes in the Cd group were lower than those in the control group. Cd can significantly reduce the expression of PI3K, AKT and HIF-1α in the three lymph nodes. In summary, Cd induces oxidative stress and regulates the PI3K/AKT/HIF-1α signal transduction pathway to cause mitochondrial dynamics disorder, which leads to the apoptosis of pig lymph nodes, suggesting that Cd-induced mitochondrial pathway apoptosis is related to Cd pig lymph nodes play an important role in the toxicity mechanism.